Heart Failure–Related Death in Subjects With Atrial Fibrillation in the United States, 1999 to 2020 - Zuin, Marco; Bertini, Matteo; Vitali, Francesco; Turakhia, Mintu; Boriani, Giuseppe (Journal of the American Heart Association, 2024)
Population-based data on heart failure (HF)-related death in patients with atrial fibrillation (AF) are lacking. We assessed HF-related death in people with AF in the United States over the past 21 years and examined differences by age, sex, race, ethnicity, urbanization, and census region. Data were extracted from the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research to determine trends in age-adjusted mortality rates per 100 000 people, due to HF-related death among subjects with AF aged ≥15 years. To calculate nationwide annual trends, we assessed the average annual percent change (AAPC) and annual percent change with relative 95% CIs using joinpoint regression. Between 1999 and 2020, 916 685 HF-related deaths (396 205 men and 520 480 women) occurred among US adults having a concomitant AF. The overall age-adjusted mortality rates increased (AAPC: +4.1% [95% CI, 3.8-4.4]; <0.001), especially after 2011 (annual percent change, +6.8% [95% CI, 6.2-7.4]; <0.001) in men (AAPC, +4.8% [95% CI, 4.4-5.1]; <0.001), in White subjects (AAPC: +4.2% [95% CI, 3.9 to 4.6]; <0.001) and in subjects aged <65 years (AAPC: +7.5% [95% CI, 6.7-8.4]; <0.001). The higher percentage of deaths were registered in the South (32.8%). During the first year of the COVID-19 pandemic, a significant excess in HF-related deaths among patients with AF aged >65 years was observed. A worrying increase in the HF-related mortality rate among patients with AF has been observed in the United States over the past 2 decades.